Windscanner.PT: National Research Infrastructure - Simões, Teresa (2021)
ABSTRACT: This document presents a contribution to the project's activities, developed under Task#4 and Task #5 of the WindScanner.PT Research Infrastructure (PINFRA/22207/2016). The main activities developed under this project were the Business Plan and Governance Structure related with legal documentation, and data processing and modelling, related with field experiments using Lidars. The Business Plan and Governance Structure are detailed in two separate reports developed by LNEG and IPB. In this sense, this report summarises the content of these two reports, and the details are presented on Annexes I and III of this document. In addition to the business plan elaboration, a budgeting tool was developed to support the RI activities and is presented in Annex II. In this project, two research fellowships were foreseen by LNEG, and both the contracted students contributed to the development of the Business Plan and Governance Structure. In addition, they have also contributed to the knowledge on data processing and modelling, using Lidar sensors and other data sources. The activities' reports are presented in Annexes IV and V of this document. Finally, this document, presents the indicators achieved at the end of the project.